The Power of Positive Selling - Strutzel, Dan; Shoblom, Traci (Ascent Audio, 2020)
Good sales relationships don't just happen. They must be nurtured and developed. From ancient trade routes to modern Internet platforms, sales is one of the world's oldest professions. Throughout the ages, there have been as many ways to sell as there are customers who want to buy. But whether you're a novice or seasoned sales person, no matter what your product or service there is one truth that crosses all boundaries in selling. Selling depends on a relationship. That relationship might last only a few minutes, or extend through an entire lifetime, but in order to conduct a sales transaction, there must be a relationship. In The Power of Positive Selling, you will: - Learn to create and maintain a true connection with your customers - Understand the sales person's, the buyer's, and the relationship perspective. - Determine how to really listen to your buyer - Identify the most effective planning methods - Discover how to handle rejection - Perfect what to say to price objections - Create an automated follow up system - Recognize the important things to know about your product.